2007
DOI: 10.2174/156652407782564363
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-Kappa B: From Clone to Clinic

Abstract: Nuclear transcription factor kappaB (NF-kappaB) was first discovered in 1986 in the nucleus of the B cell as an enhancer in the kappa immunoglobulin chain. However, this factor has identified in the cytoplasm in the resting state. When activated in response to inflammatory stimuli, carcinogens, stress, ionizing radiation, and growth factors; NF-kappaB translocates to the nucleus where it upregulates the expression of over 400 different gene products linked with inflammation, cell survival, proliferation, invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 108 publications
(119 reference statements)
3
87
0
1
Order By: Relevance
“…In general, NF-kB may form a hetero-dimer with any one of the five members, including p65, p50, p52, cRel and RelB, depending upon the cell type and nature of stimulation (Ahn et al, 2007). As shown previously (Supplementary Figure S1B), TCEAL7-downregulated OSEtsT/hTERT clones (C4-2 and C4-4) showed higher amounts of NF-kB complex when compared with vector clone V1.…”
Section: Mechanism Of Tceal7-mediated Regulation Of Nf-kb Pathwaysupporting
confidence: 68%
See 1 more Smart Citation
“…In general, NF-kB may form a hetero-dimer with any one of the five members, including p65, p50, p52, cRel and RelB, depending upon the cell type and nature of stimulation (Ahn et al, 2007). As shown previously (Supplementary Figure S1B), TCEAL7-downregulated OSEtsT/hTERT clones (C4-2 and C4-4) showed higher amounts of NF-kB complex when compared with vector clone V1.…”
Section: Mechanism Of Tceal7-mediated Regulation Of Nf-kb Pathwaysupporting
confidence: 68%
“…The mechanism by which TCEAL7 modulates p300-p65 interaction is currently unknown. The transcription factor complexes of NF-kB are one of the most widely studied in cancer because of their widespread de-regulation and transcriptional control of numerous genes that produce cytokines, chemokines, growth factors and anti-apoptotic factors that aid in the progression, maintenance and also chemoresistance of various tumors including ovarian tumors (Karin, 2006;Ahn et al, 2007). Downregulation of TCEAL7 in OSEtsT/hTERT cells promoted transcription factor activity of several transcription factors, including NF-kB (Chien et al, 2008), which translated into significantly increased NF-kB reporter activity and DNA binding in OSEtsT/hTERT clones with stably downregulated TCEAL7 expression compared with vector clones expressing TCEAL7.…”
Section: Discussionmentioning
confidence: 99%
“…ING4 has been recently proposed to complex with the large subunit of NF-κB and to inhibit NF-κB-mediated transactivation of gene expression (7). As NF-κB plays a role in multiple biological processes, including angiogenesis, apoptosis, and the innate and adaptive immune response (26,27), regulation of NF-κB by Ing4 might also impact tumor formation. To examine the ability of Ing4 to regulate NF-κB activity in vivo, we examined the innate immune response of Ing4 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear expression of NF-kB might be considered as an indicator of malignant transformation and, interestingly, it is well demonstrated that NF-kB is constitutively activated during human cervical cancer progression (Nair et al, 2003). Reports also indicate that inhibition of NF-kB ameliorates the pathogenesis and overcomes therapeutic resistance (Ahn et al, 2007). Moreover, paclitaxel induces NF-kB activation in several cell types, and adjuvants that inhibit NF-kB function can enhance its therapeutic efficiency (Bava et al, 2005;Logan et al, 2007;Inoue et al, 2008).…”
Section: Discussionmentioning
confidence: 99%